Provisional Technique for Bifurcation Left Main In-Stent Restenosis Lesion: A Case Report - Krishna Ari Nugraha; Sasmojo Widito; Budi Satrijo; Novi Kurnianingsih (Heart Science Journal, 2022)
BackgroundPercutaneous coronary intervention for bifurcation lesions remains challenging because of its complexity and the lack of trials to guide decision-making. Interventional cardiologists are forced to make decisions based on their own judgment and experience rather than the results of rigorously randomized trials.Case SummaryA 64-year-old male with some coronary risk factors of hypertension, passive smoker, and family history of CAD presented with recurring exertional chest pain for the last 4 months. He was hospitalized to undergo DCA-Adhoc after the ECG stress test revealed a positive result. The coronary angiography revealed a 95% ISR in the osteal LAD and 20% ISR of the proximal LCx. Since the patient refused to undergo coronary bypass surgery, the team decided to perform catheter intervention to the LM bifurcation of LAD-LCx. The procedure begins with the insertion of IABP through the access of the left femoral artery. We performed a provisional approach with the main vessel stenting of LM-LAD. At the end of the procedure, we performed simultaneous kissing balloon inflation of LAD-LCx followed by POT in LM stent as the post-dilation procedure.DiscussionWhen considering intervention on a bifurcation lesion, there are two general strategies i.e the more conservative or provisional technique that intent to only use one stent and the two-stent approach. The provisional technique is considered to offer advantages in terms of reducing procedure complexity, reducing fluoroscopic time, requiring less contrast volume, and reducing resource (stent) use compared by 2 stent strategy.